Prognostic value of tumoral expression of galectin-9 in gastric cancer - Choi, Sang Il; Seo, Ki-woo; Kook, Myeong-Cherl; Kim, Chan Gyoo; Kim, Young-Woo; Cho, Soo-Jeong (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Galectin-9 (Gal-9) is a member of the β-galactoside-binding lectin family. Our previous study revealed that Gal-9 suppresses migration, invasion, and epithelial-mesenchymal transition in gastric cancer cells. Gal-9 was reported to have anti-metastatic activity in patients with malignant melanoma, breast cancer, and hepatocellular carcinoma. Therefore, we aimed to evaluate the prognostic significance of Gal-9 in patients with gastric cancer. Materials and Methods: The clinical significance of Gal-9 was explored using clinical and pathological data from 619 patients with gastric cancer who underwent gastrectomy at National Cancer Center, Korea. Tissue microarray and immunohistochemical analyses were used to evaluate Gal-9 expression. The median follow-up duration was 65.7 months (range 0-79 months). Kaplan-Meier method was used to evaluate survival. Log-rank test was used to assess the differences in survival. Results: Based on the tumoral expression of Gal-9, 619 patients with gastric cancer were classified into two groups: Gal-9-positive patients (327, 52.8%) and Gal-9-negative patients (292, 47.2%). The Gal-9-positive group had a significantly lower overall (p=0.001, by log-rank test) and gastric cancer-specific mortalities (p<0.001) compared to the Gal-9-negative group. In multivariate analysis, which included the depth of invasion and lymph-node metastasis, Gal-9 positivity showed a trend toward improved prognosis but did not reach statistical significance (hazard ratio, 0.8; 95% confidence interval, 0.55-1.31). Conclusion: Tumoral expression of Gal-9 may suppress tumor progression in patients with gastric cancer.